Achieving balanced mechanical properties in Fe–0.16C plain low-carbon steel by trimodal microstructure and fine cementite - Somayyeh Gholamalipour; Roohollah Jamaati; Seyed Jamal Hosseinipour (Journal of Materials Research and Technology)
In the present study, for the first time, a trimodal microstructure (including coarse, fine, and ultrafine ferrite grains) was created in plain low-carbon steel by simple thermomechanical processing including intercritical annealing (at 770 °C, 800 °C, and 830 °C), 75% cold rolling, and finally heat treatment at 550 °C. The results showed that martensite with two different morphologies consisting of lath (low-carbon) and plate (high-carbon) were created in the microstructures of 800-75% and 830-75% sheets due to the non-homogeneous distribution of carbon atoms as a result of not using the homogenization treatment. After the final heat treatment, the samples exhibited trimodal grain size distribution of ferrite including coarse grains (larger than 5 μm), fine grains (between 1 and 5 μm), and ultrafine grains (UFGs) (smaller than 1 μm). The formation of ultrafine grains was ascribed to the presence of martensite with lath morphology in the 800-75% and 830-75% samples. The size of cementite particles in the 770-75%-550 sample was larger than the other two samples (800-75%-550 and 830-75%-550) owing to the presence of martensite phase only with plate morphology in 770-75%-550 steel. Unlike the 800-75%-550 sheet, the entire microstructure of the 770-75%-550 and 830-75%-550 samples had not undergone complete recrystallization and several deformed ferrite grains were still visible in the microstructures. The strength and hardness of the heat-treated sheets was larger than that of the as-received steel due to the presence of fine spherical cementite particles and fine ferrite grains in the microstructure of the heat-treated samples. Based on the obtained results, the 800-75%-550 sample revealed the best combination of strength-ductility-toughness due to trimodal microstructure along with the formation of fine spherical cementite particles. The failure mode of all heat-treated samples was ductile and there were both fine and coarse dimples in the fracture surfaces.